Caves, plazas, and Gods: the impact of geomorphology on Taino utilization of ceremonial sites - Schwantes, Katharine (My University, 2011)
The Classic Taino culture was spread across Puerto Rico and Hispaniola. Their shamanistic religious beliefs included spirits and gods, referred to as zemis, which were tied into the landscape. Geology had influence on not only the placement of ceremonial sites, but also the ways in which these sites were used. In this study, special attention was paid to four sites, El Manantial de la Aleta, Caguana, Cueva Lucero, and Atajadizo, which contrast different aspects of geographical settings. These sites were compared in two ways, first on a larger scale in relation to the surrounding landscape and other similar sites. Also considered were the individual sites in relation to their counterparts, taking into account aspects such as artifact occurrence and usage of space within the sites to ascertain the differences between the two sites and what role the geology of the site may have played in influencing utilization.
Keywords: Aleta, Manantial de la (Dominican Republic); Excavations (Archaeology) -- Dominican Republic.; Taino Indians.; Hispaniola -- History.; Puerto Rico -- Antiquities.; Archaeology and history -- Puerto Rico.; Archaeology -- Methodology.